The justice lottery?: police station advice 25 years on from PACE - Pleasence, Pascoe; Kemp, Vicky; Balmer, Nigel (Sweet and Maxwell, 2011)
January 2011 marks the 25th anniversary of the introduction of the unequivocal right of police station detainees to obtain advice from a solicitor. However, while this right is a fundamental safeguard to procedural propriety, no large-scale investigation of the rates at which advice is requested or received has been undertaken in over a decade. This study, the most extensive yet undertaken, draws on data extracted from 30,921 custody records, across 44 police stations in 4 police force areas. We find the advice request rate has risen less than recent studies indicate. We also find substantial variation in request rates between police stations and police forces, after accounting for other factors, and a sharp drop in the request rate between ages 16 and 17. This drop supports proposals to extend requirements around appropriate adults to 17 year olds. We argue that, at a time of change in police station operation and advice provision, further monitoring of, and investigation into, the operation of the right to advice is required. © 2011 Thomson Reuters (Legal) Limited.